Influence of Genomics on Cancer Vaccine Development - from Guess to Prediction - Schultze, J.L.; Bohlen, H. (Current Pharmaceutical Design, 2002)
After more than 100 years since the first adjuvant for a cancer vaccine was described and more than a decade since the first tumor antigen has been molecularly cloned, it seems possible that cancer vaccines might be integrated into the standard care of cancer patients. Exciting new technologies concerning tumor antigen discovery, vaccine delivery and formulation define the basis for enormous efforts in academia as well as in the pharmaceutical and biotech industry. With the unveiling of the human genome additional targets will emerge that could further enhance vaccine efficacy, specificity and clinical applicability. Most likely therefore, tumor antigen targets which are widely expressed in cancer will be of advantage over patient-oriented approaches due to their favorable cost-to-benefit ratio. Some widely expressed candidate tumor antigens and methods to discover additional widely expressed tumor antigens are discussed here. While the armamentarium of potential tools to cancer vaccine development seems to be endless, only those that are scientifically sound yet economically reasonable will - in the end - have a chance to become clinically useful cancer vaccines.
Keywords: murine models